2014
DOI: 10.7314/apjcp.2014.15.5.2115
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Hydrazinocurcumin on Carcinogenesis of Diethylnitrosamine-induced Hepatocarcinoma in Male SD Rats

Abstract: The purpose of the present study was to evaluate the preventive effects of hydrazinocurcumin (HZC) on diethylnitrosamine (DEN)-induced hepatocarcinogenesis in a male Sprague Dawley (SD) rat model. One hundred and twenty male SD rats used in this study were divided into six groups. Those receiving DEN with curcumin (CUR) or HZC were studied compared with the DEN-alone group. The study demonstrated that DEN induced severe histological and immunohistochemical changes in liver tissues, significantly increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
7
18
0
Order By: Relevance
“…Since the serum ALT and AST can better reflect the extent of liver damage, they are the key indexes measuring the level of liver injury. Zhao JA et al (2014) demonstrated that diethylnitrosamine (DEN) induced severe histological and immunohistochemical changes in liver tissues, significantly increasing the levels of liver marker enzymes such as ALT and AST. Taken together, their results suggested application of curcumin (CUR) and hydrazinocurcumin (HZC) could prevent the occurrence of carcinogenesis and HZC may be a more potent compound for prevention of DEN-induced hepatocarcinogenesis in rats than CUR (Zhao JA et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the serum ALT and AST can better reflect the extent of liver damage, they are the key indexes measuring the level of liver injury. Zhao JA et al (2014) demonstrated that diethylnitrosamine (DEN) induced severe histological and immunohistochemical changes in liver tissues, significantly increasing the levels of liver marker enzymes such as ALT and AST. Taken together, their results suggested application of curcumin (CUR) and hydrazinocurcumin (HZC) could prevent the occurrence of carcinogenesis and HZC may be a more potent compound for prevention of DEN-induced hepatocarcinogenesis in rats than CUR (Zhao JA et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao JA et al (2014) demonstrated that diethylnitrosamine (DEN) induced severe histological and immunohistochemical changes in liver tissues, significantly increasing the levels of liver marker enzymes such as ALT and AST. Taken together, their results suggested application of curcumin (CUR) and hydrazinocurcumin (HZC) could prevent the occurrence of carcinogenesis and HZC may be a more potent compound for prevention of DEN-induced hepatocarcinogenesis in rats than CUR (Zhao JA et al, 2014). Duh PD et al (2010) investigated the in vitro and in vivo protective effects of water extract of pu-erh tea (WEPT) on tert-butyl-hydroperoxide (t-BHP)-induced oxidative damage in hepatocytes of HepG2 cells and in rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…ALP level elevates linearly with the tumour mass and is considered to be important marker during diagnosis in early detection of cancer. 27 MESA at dose of 200 mg/kg and 400 mg/kg decreased the elevated levels of these biochemical parameters in a dose dependant manner. Extract tends to prevent liver damage by maintaining integrity of plasma membrane thereby supressing the leakage of enzyme through membranes, exhibiting hepatoprotective activity.…”
Section: Histopathological Examination Of Hepatic Tissuesmentioning
confidence: 85%
“…SK-HEP-1 cells were seeded in 6-well plates at a density of 5x10 5 cells/well for 24 h at 37˚C, incubated with 20 µM Z-DEVD-FMK (Santa Cruz Biotechnology Inc., Santa Cruz, CA, USA) or vehicle for 1 h, followed by treatment with various concentrations of GL63 and CUR (0, 10, 20 and 40 µM) for 24 h. All cells were collected and washed twice with cold PBS. Next, the cells were collected and resuspended in 100 µl binding buffer containing annexin V and PI.…”
Section: -(45-dimethylthiazol-2-yl)-25-diphenyltetrazolium Bromidementioning
confidence: 99%
“…However, this can be performed only in selected patients whose tumors are small and located away from major vessels and have not metastasized to extrahepatic organs (4). No chemotherapy agent has better benefit than surgery in controlled clinical trials due to different reasons, including drug resistance and toxicity to normal cells (5).…”
Section: Introductionmentioning
confidence: 99%